Learning through games in mathematics teaching - Teokarević Dalibor D. (Sinteze, 2024)
Of all the human activities, the game gives a person the most pleasure. Whether it's sports, computer, social, educational or other games, people are happy to get involved in their implementation. As the game is one of the most important needs of children, it is also the most effective way to bring the teaching contents closer to the students. One learns through the game, because based on the rules, settings and own skills, existing and new concepts and relationships between them are defined. That is why learning through play is one of the most productive teaching methods, which encourages students' creativity, logical thinking, emotional expression and motivation for work and learning. Learning through play also affects the all-round development of the student's personality, as it encourages the child's cognitive, emotional, social and physical development. In this way, it comprehensively prepares him for his future life in the world of adults.